Environmental Impacts of Blue Economy Initiatives: A Bibliometric Review - Apriantoro, Muhamad Subhi; Bintang, Aureylia Cinta Sekar (International Journal of Energy Economics and Policy, 2026)
Studies on the blue economy are no longer just a national issue, but have become a major global concern. This study aims to affirm global commitment to blue economy initiatives that align with the economic sector, marine ecosystems, and community welfare within the Sustainable Development Goals (SDGs) framework. Using a bibliometric approach, this study maps research development, identifies trends and key topics, and evaluates gaps based on the Scopus database from 2016 to 2025. The results indicate an increase in publications over the past five years, particularly in the areas of sustainable fisheries, marine conservation, and renewable marine energy. Although the economic contributions of the blue economy are increasingly recognized, damage to marine ecosystems from unsustainable practices remains a challenge. Therefore, balancing economic growth with environmental conservation is necessary. The originality of this study lies in its emphasis on less-explored topics, such as blue carbon and socio-economic integration, which can inform future research efforts.